Interplay Between Diabetes and Pancreatic Ductal Adenocarcinoma and Insulinoma: The Role of Aging, Genetic Factors, and Obesity - Duvillié, Bertrand; Kourdoughli, Rayane; Druillennec, Sabine; Eychène, Alain; Pouponnot, Celio (Frontiers in Endocrinology, 2020)
Epidemiologic analyses have shed light on an association between type 2 diabetes (T2D) and pancreatic ductal adenocarcinoma (PDAC). Recent data also suggest a potential relationship between T2D and insulinoma. Under rare circumstances, type 1 diabetes (T1D) can also be implicated in tumorigenesis. The biological mechanisms underlying such relationships are extremely complex. Some genetic factors contributing to the development of T2D are shared with pancreatic exocrine and endocrine tumors. Obesity and overweight can also contribute to the initiation and severity of T2D, while aging may influence both endocrine and exocrine tumors. Finally, pharmacological treatments of T2D may have an impact on PDAC. On the other hand, some treatments for insulinoma can trigger diabetes. In the present minireview, we discuss the cellular and molecular mechanisms that could explain these interactions. This analysis may help to define new potential therapeutic strategies.